The Effect of Democratic Leadership Style on Employee Performance at PDpark Makassar Raya - Isgunandar, Isgunandar; Mulyani, Ika; Niswaty, Risma (Universitas Negeri Makassar, 2022)
Leadership is an important element in a company, because without leadership a company will experience setbacks. A leader has different characteristics in leading his subordinates. This leader's behavior is called leadership style. This study aims to determine the effect of democratic leadership style on the performance of employees in PD. Greater Makassar Parking. This research is a quantitative research that shows causation. The sample in this study were 51 people using the Simple Random Sampling technique and 3 informants. Data collection techniques used are questionnaires, interviews, and documentation. The data analysis technique used is descriptive data analysis and inferential statistical analysis. Based on the results of the product moment correlation test, the relationship between variables is moderate. The results showed that the democratic leadership style was in the